Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Para resolver el problema, primero vamos a evaluar la función [tex]\( g(x) = -3(x-2)^2 + 6 \)[/tex] en el punto [tex]\( x = -1 \)[/tex].
1. Sustituyamos [tex]\( x = -1 \)[/tex] en la expresión:
[tex]\[ g(-1) = -3(-1 - 2)^2 + 6 \][/tex]
2. Simplifiquemos el término dentro del paréntesis:
[tex]\[ -1 - 2 = -3 \][/tex]
3. Elevemos al cuadrado el resultado obtenido:
[tex]\[ (-3)^2 = 9 \][/tex]
4. Multipliquemos por [tex]\(-3\)[/tex]:
[tex]\[ -3 \cdot 9 = -27 \][/tex]
5. Finalmente, sumemos 6:
[tex]\[ -27 + 6 = -21 \][/tex]
Por lo tanto, hemos calculado que [tex]\( g(-1) = -21 \)[/tex].
Ahora, necesitamos calcular [tex]\( -\frac{g(-1)}{3} \)[/tex]:
1. Sustituimos [tex]\( g(-1) \)[/tex] con el valor que acabamos de encontrar:
[tex]\[ -\frac{-21}{3} \][/tex]
2. Simplificamos la fracción:
[tex]\[ -\left( -7 \right) = 7 \][/tex]
Entonces, el valor de [tex]\( -\frac{g(-1)}{3} \)[/tex] es [tex]\( 7 \)[/tex].
Por lo tanto, la respuesta final es [tex]\( \boxed{7} \)[/tex].
1. Sustituyamos [tex]\( x = -1 \)[/tex] en la expresión:
[tex]\[ g(-1) = -3(-1 - 2)^2 + 6 \][/tex]
2. Simplifiquemos el término dentro del paréntesis:
[tex]\[ -1 - 2 = -3 \][/tex]
3. Elevemos al cuadrado el resultado obtenido:
[tex]\[ (-3)^2 = 9 \][/tex]
4. Multipliquemos por [tex]\(-3\)[/tex]:
[tex]\[ -3 \cdot 9 = -27 \][/tex]
5. Finalmente, sumemos 6:
[tex]\[ -27 + 6 = -21 \][/tex]
Por lo tanto, hemos calculado que [tex]\( g(-1) = -21 \)[/tex].
Ahora, necesitamos calcular [tex]\( -\frac{g(-1)}{3} \)[/tex]:
1. Sustituimos [tex]\( g(-1) \)[/tex] con el valor que acabamos de encontrar:
[tex]\[ -\frac{-21}{3} \][/tex]
2. Simplificamos la fracción:
[tex]\[ -\left( -7 \right) = 7 \][/tex]
Entonces, el valor de [tex]\( -\frac{g(-1)}{3} \)[/tex] es [tex]\( 7 \)[/tex].
Por lo tanto, la respuesta final es [tex]\( \boxed{7} \)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.